Re-inventing CARICOM : the road to a new integration : a documentary record - Hall, Kenneth O. (Ian Randle KingstonJM, 2003)
Records the history and evolution of the Caribbean Community. Analyzes the reasons for the establishment of CARICOM and makes available excerpts of the reports of Heads of Government Conferences. Provides full drafts of major declarations and treaties.